Study on Deposit Mobilization for Readymade Garments Workers in Bangladesh - International Finance Corporation (International Finance Corporation, Dhaka, Bangladesh, 2017)
For a developing country like Bangladesh, the readymade garments (RMG) sector is the country's primary foreign exchange revenue generator. It has provided employment to about three million workers, with 85 percent being young, poor and semi-literate women. The sector is growing at sixteen percent annually, but workers cannot leverage this effectively, as they lack access to suitable financial services and face security risks due to receiving wages in cash. The recent developments in banking technology have transformed banking from the traditional brick-and-mortar infrastructure of staffed branches to a system supplemented by other channels like automated teller machines (ATM), credit or debit cards, internet banking, online money transfers, etc. Access to such technology, however, is still restricted only to certain segments of the society. For the financially excluded such as RMG workers, small entrepreneurs, etc., opening and maintaining bank accounts, especially in a country like Bangladesh, can be complex and time-consuming due to lack of awareness, accessibility and availability of targeted products. As part of its agenda to promote financial inclusion in Bangladesh, IFC is focused on providing access to finance to underserved segments through building the financial sector’s awareness. This report highlights key trends, challenges, and opportunities for banking services for RMG workers and increasing their access to finance. Due to their high growth potential of the sector, RMG employees are of particular interest. The report therefore identifies: (i) constraints and opportunities for scalable approaches to increase access to finance for RMG employees; (ii) pinpoint specific knowledge gaps for which further training is recommended; and (iii) provide recommendations on expanding access to finance for RMG employees.